PERSEPSI MAHASISWA TERHADAP RADIKALISME (Studi Penelitian Deskriptif di UIN Sunan Kalijaga Yogyakarta) - Mahardika, Rizky Eka; Assingkily, Muhammad Shaleh; Kamala, Izzatin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2020)
Da'wah, Jihad, and Islam are a partial correlation. Da'wah is seen differently by everyone, Similarly, jihad is always synonymous with acts of violence. Jihad is not a taboo in the present because it already existed in the time of Muhammad Saw. Students become resource persons in research. The results of the study revealed that: 1. Da'wah is actually a da'wah that uses ethics of courtesy by ruling out acts of violence. In diversity is primary in preaching, not individuality. 2. Jihad in the teachings of Islam is to sacrifice one's body and soul in fighting for and upholding the teachings of Allah. However, many jihadis are misinterpreted that the act of defending religion with terrorists. 3. The perception that Islam is identical with the violence of views which is not justified in Islam because Islam itself is not a religion of violence but a tolerant religion. The perpetrators of radicalism are themselves individuals or groups not in the name of Islam.